PROPOSED MULTI MANNED ASSEMBLY LINE BALANCING AS PRODUCTION SYSTEM IN AIRCRAFT INDUSTRY (The Indonesian Journal of Business Administration, 2019)
PT Dirgantara Indonesia use project layouts in their production systems. With projects layout the risk of late delivery are quite high. The average production duration with a project layout is 10 months with a standard deviation of 4.22 months and coefficient of variance 43.95% which show unstable production duration.The application of MMALB can be a solution to this problem. Assembly line balancing (ALB) is a tool in operation that is used to divide production activities into workstations. In a single ALB, there is one worker in a work station whereas in Multi Manned Assembly Line Balancing (MMALB), there are more than one worker in a workstation. The whole process of assigning production activities into workstations use heuristic algorithmAs a result, there are eight workstations required, with eachwork station filled with production activities which each production activity has been registered in the team. The average production duration with MMALB is 250 hours/ 2 months with standard deviation 13.18 hours,  and coefficient of variance 5.23%. Efficiency level of MMALB configuration is 81%. It can be concluded that MMALB provides faster production takt time with more stable production duration compare to project layout.Keywords:  Assembly line balancing, Multi Manned Assembly Line Balancing, Cycle Time, Efficiency, Standard Deviation